Caenorhabditis elegans as a Model Organism for Special Environment - Cosme, Shania Jeanne; Agustin, Maria Alysha Nicole; Remedios, Francesca Louise; Dianko, Camille Jedidiah; Ungria, Florielie; Villanueva, Stacey Loraine; Nas, John Sylvester (Asian Journal of Biological and Life Sciences)
Organisms living in special environments, namely deep-sea, high altitude, and space environment experience physiological, biochemical, and genetic changes. Human study in special environments may be time consuming and expensive, hence, the authors are proposing the use of Caenorhabditis elegans (C. elegans). This non-parasitic nematode has been widely used as model organism for various human diseases, such as cancer, neurodegenerative disorders, and aging-associated diseases. There are also physiological and biochemical parameters in humans established in C. elegans. Similarly, C. elegans carry ortholog genes that are associated with human genes. This paper reviews the physiological, biochemical, and genetic changes in humans under the different special environments and correlate these effects in the current understanding of the special environments in C. elegans. Both the deep-sea and high-altitude environment leads to hypoxia due to do the decrease in oxygen supply in humans. Hypoxia in C. elegans is regulated by p38 mitogen activated protein kinase (MAPK), which inhibits the oxygen sensor EGL-9 and activates hypoxia-inducible factor 1 (HIF-1). In space environment, humans and C. elegans experience are observed to have decreased muscle mass. The muscle morphogenesis in humans is associated with MyoD, which interestingly has a counterpart in C. elegans, ceMyoD. Even though there were studies using C. elegans in different special environments, there were some physiological and biochemical changes that are still not elucidated. It is interesting to study the effects of these different special environments by mimicking various environmental conditions on the lifespan and health span in C. elegans.
Keywords: Caenorhabditis elegans; Deep-sea; High altitude; Humans; Space; Special environments